Analisis Inflasi Indonesia Jangka Panjang: Kajian Terhadap Faktor-Faktor Luar Negeri - Suriani Suriani; Syarifah Nurul Asra (Syiah Kuala University, 2014)
he purpose of this study is to determine the effect of the exchange rate, foreign inflation, and world oil prices on the rate of inflation in Indonesia in the long run. The data used are secondary data in the form of monthly from January 2000 to December 2012. The Model used in this study is a Vector Error Correction Model (VECM) to determine the estimation of short- term, and using the Johansen cointegration test to determine the long-term relationship between variables.This study revealed that in the long term there is a cointegration relationship among the variables. In the short term, the variables affecting the world oil prices and have a causal relationship with inflation, while the variable exchange rate and foreign inflation does not affect and does not have a causal relationship with the Indonesian inflation. Expected on the government to further consider trade policies in the purchase of imported goods, especially for oil imports given considering the influence of fluctuations in world oil prices affect inflation in Indonesia in the short term as well long term.